Thrombus migration in intracranial large vessel occlusion: course, predictors, and impact on endovascular thrombectomy - Eun, Mi-Yeon; Choi, Woochan; Hwang, Yang-Ha; Kim, Kwang Hyun; Kim, Yong-Won (Frontiers in Neurology, 2025)
IntroductionThrombus migration (TM) is occasionally observed in patients with acute ischemic stroke undergoing endovascular thrombectomy (EVT) for large vessel occlusion. However, the predictors and clinical implications of TM remain unclear. This study aimed to identify clinical and radiological factors associated with TM and assess its impact on procedural and functional outcomes.Materials and methodsWe retrospectively analyzed 348 patients with intracranial large vessel occlusion (ICA, M1, or M2) treated with EVT at two comprehensive stroke centers. TM was defined as a distal shift of the thrombus location between CT angiography and digital subtraction angiography. Predictors of TM were determined using multivariable logistic regression. Procedural and clinical outcomes were compared between the TM and non-TM groups.ResultsTM was observed in 77 patients (22.1%), with 32 patients showing migration beyond the vessel segment. In the multivariable analysis, hyperdense artery sign [HAS; adjusted odds ratio (OR), 4.68; 95% confidence interval (CI), 2.62–8.34], diastolic blood pressure (adjusted OR, 0.98; 95% CI, 0.96–1), and onset-to-arrival time per 60 min (adjusted OR, 0.87; 95% CI, 0.79–0.97) were associated with TM. The TM group showed greater NIHSS improvement, with a trend toward higher first-pass effect rates. Parenchymal hemorrhage was more frequent in the TM group. However, successful reperfusion and 3-month functional outcomes were comparable between groups.ConclusionIn patients with intracranial large vessel occlusion, HAS, diastolic blood pressure, and onset-to-arrival time were associated with TM. These findings suggest a role for thrombus composition in the TM. Radiologic and clinical outcomes were comparable in the TM and non-TM groups.